Seen and Heard in Mexico : Children and Revolutionary Cultural Nationalism - Albarrán, Elena Jackson (Book collections on Project MUSE., 2014)
During the first two decades following the Mexican Revolution, children in the country gained unprecedented consideration as viable cultural critics, social actors, and subjects of reform. Not only did they become central to the reform agenda of the revolutionary nationalist government; they were also the beneficiaries of the largest percentage of the national budget. While most historical accounts of postrevolutionary Mexico omit discussion of how children themselves experienced and perceived the sudden onslaught of resources and attention, Elena Jackson Albarrán, in Seen and Heard in Mexico, places children's voices at the center of her analysis. Albarrán draws on archived records of children's experiences in the form of letters, stories, scripts, drawings, interviews, presentations, and homework assignments to explore how Mexican childhood, despite the hopeful visions of revolutionary ideologues, was not a uniform experience set against the monolithic backdrop of cultural nationalism, but rather was varied and uneven. Moving children from the aesthetic to the political realm, Albarrán situates them in their rightful place at the center of Mexico's revolutionary narrative by examining the avenues through which children contributed to ideas about citizenship and nation.